The Debt Policy and Performance of State-Owned Companies in Indonesia - Sinurat, Mangasi; Ilham, Rico Nur; Sinta, Irada; Ahmad, Shabir (Universitas Muhammadiyah Yogyakarta, 2024)
Research Aims: This research aims to explore the factors influencing debt policy in